Postpartum hemorrhage caused by uterine artery pseudoaneurysm: A case report - Danielle Glassman; Ruchi Karsalia; Issam Moubarak; Mark V. Sauer; Ashima Singla (Elsevier, 2021)
Background: Uterine artery pseudoaneurysms (UAPs) are a rare life-threatening complication presenting as vaginal bleeding. Transvaginal ultrasound doppler scans can diagnose UAPs in the immediate and later postpartum period. This case report highlights UAP management using minimally invasive interventions for fertility preservation. Case: A 21-year-old woman presented on post-operative day 10 following a primary cesarean section with heavy vaginal bleeding and a UAP was confirmed on doppler sonography. A multidisciplinary approach determined the optimal management taking the patient's fertility into consideration. Initially, the UAP was injected directly with thrombin under ultrasound guidance. However, due to a subsequent hemorrhage, a uterine artery embolization was performed. Conclusion: Recognition of UAP is critical in the management of postpartum vaginal bleeding. Patient goals should be balanced with the severity of UAPs to determine optimal management.